IDENTIFICATION AND ANALYSIS OF THE PROBLEMS OF GENDER MAIN STREAMING IN AGRICULTURAL DECISION MAKING AND EXTENSION WORK: A CASE STUDY OF DISTRICT CHAKWAL - F. Nosheen; M. Ahmad; M. Ishaque (Journal of Animal and Plant Sciences, 2010)
Gender mainstreaming of women is more than a political process that would enable women to participate equally with men in all spheres of life and at all levels of decision making so that their different needs could be equally addressed. In Pakistan, it was, therefore, imperative to conduct a study to find out the problems being faced in gander mainstreaming and their possible solution in the rain fed area of Chakwal district. Total 400 respondents (200 husbands and 200 wives) were selected in District Chakwal taken as universe through simple random sampling technique and adopting multi stage random sampling approach. Twenty households were randomly selected from each selected village for formal interview purposes. The married couple from each household was interviewed during the formal survey. The data acquired from the field were transferred in the Microsoft Excel and SPSS in order to summarize the gathered data and chi squared distribution was applied with single degree of freedom. Turning to gender equality problems faced in the society, the most reported problem reported by wives was gender specific work (91.5 % ), male dominant society ( 89.5 %) and lack of job opportunities (88.5 % ) for the females in the area. The husbands reported reasons slightly differently as lesser opportunities for women (86 %), cultural values (87 %), less recognition of women work (86 %) and male dominance in the society (85.5 %). The low intensity problems reported by male and female respondents were giving more weight to cultural values and low level of literacy among women. It is, therefore, suggested that female children should be encouraged to acquire higher education, non-governmental organizations (NGOs) working in the area should promote gender equality and the financial institutions should be emphasized to extend small loans to women folk to bring them in gender main streamline in agricultural decision and extension work.
Keywords: Gender mainstreaming; problems; identification; solutions